(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Seed dressing chemicals play a critical role in enhancing seed quality and protecting against seed–borne pathogens with varying effects on germination and seedling growth. This study evaluated the impact of different seed dressing treatments on germination and early growth parameters. A variety of bell peppers and three seed dressing chemicals (Imidacloprid 20% + Metalaxyl –M 20% + Tebuconazole 2% WS, Imidacloprid 20% + Metalaxyl 20% and Imidacloprid 10% + Thiram 10%) were tested. Final germination percentage, mean germination time, germination rate index, germination energy, germination index, and seedling growth parameters were investigated to determine the effectiveness of the seed dressing chemicals. Results showed that the control, Imidacloprid 20% + Metalaxyl 20% and Imidacloprid 10% + Thiram 10% treatments maintained relatively high germination performance. However, Imidacloprid 20% + Metalaxyl –M 20% + Tebuconazole 2% WS drastically reduced germination (5.00%) and all other germination indices, indicating severe toxicity. Similarly, Imidacloprid 20% + Metalaxyl –M 20% + Tebuconazole 2% WS had the most detrimental effects on seedling growth, resulting in a significantly reduced plumule length (0.04 cm), radicle length (0.98 cm), and SVI (15.25). Conversely, Imidacloprid 20% + Metalaxyl 20% exhibited comparable performance to the control in both germination and seedling vigour, while Imidacloprid 10% + Thiram 10% showed moderate inhibitory effects on root and shoot development. Conclusively, these findings suggest that Imidacloprid 20% + Metalaxyl 20% is a promising seed dressing chemical, while Imidacloprid 20% + Metalaxyl –M 20% + Tebuconazole 2% WS has a strong inhibitory effect and should be avoided or reformulated.